An Empirical Investigation Examining the Target Capital Structure of US Firms - Lin, Tong (2011)
Capital structure is one of the most controversial topics in corporate finance. There are numerous theories and hundreds of empirical studies that have been undertaken in this field, but there is currently no universally agreed theory until now. The aim of this study is to contribute to a greater understanding of the US target capital structure of various industries based on the most recent data obtained from US companies. This utilizes data from 348 US firms across 7 industries from Standard and Poor 500 (S&P 500) obtained over an 8-year period 2003 to 2010. A simple regression analysis was implemented developed from a partial adjustment model to investigate two questions: whether or not US firms adjust their long term debt ratio towards the industry mean level; whether there is any difference in target capital structure adjustment between pre-crisis period(2003-2006) and post-crisis period(2007-2010). The results here demonstrate weak support for the notion that the debt ratios of the firms in our sample adjust towards the industry mean level. But there is evidence that there is significant difference between the target capital structure adjustment between pre-crisis period and post-crisis period. Although several limitations exist, the findings here could have implications for firms considering their capital structure decisions between debt and equity financing. This study may help financial managers to better understand trends in capital structure decisions across a whole industry in recent years, and provide some indication of what the market was anticipating.